Pesticide Formulations and Application Systems: 17th Volume 1997
DOI: 10.1520/stp13847s
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Chemistry Affects Surfactant Phytotoxicity and Enhancement of Herbicide Efficacy

Abstract: Nonionic surfactants are comprised of a lipophilic and a hydrophilic moiety. Experiments were conducted to determine the effect of the lipophilic moiety on droplet spread; surfactant phytotoxicity, and surfactant enhancement of herbicide phytotoxicity. Six different lipophilic moieties and two herbicides were evaluated on four plant species. Each lipophilic moiety was represented by two surfactants: one with a low hydrophilic:lipophilic balance (HLB) value, near 12.0, and one with a high HLB value, near 16.0. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previous studies have also suggested a relationship between the surfactant HLB and the water solubility of the herbicide (Smith et al 1966;Stevens and Bukovac 1985;Holloway and Stock 1990;Manthey et al 1997). Unfortunately, surfactant prescription using this relationship is not possible for most surfactant products because manufacturers do not disclose the degree of ethoxylation or HLB.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also suggested a relationship between the surfactant HLB and the water solubility of the herbicide (Smith et al 1966;Stevens and Bukovac 1985;Holloway and Stock 1990;Manthey et al 1997). Unfortunately, surfactant prescription using this relationship is not possible for most surfactant products because manufacturers do not disclose the degree of ethoxylation or HLB.…”
Section: Resultsmentioning
confidence: 99%
“…The MVO adjuvants enhance herbicide absorption by disrupting or softening the cuticular waxes and by increasing leaf cell membrane permeability (Manthey and Nalewaja 1992). Greater droplet spread was observed as MVO concentration increased (data not shown); however, previous studies have found a poor relationship between droplet spread and herbicide phytotoxicity (Manthey et al 1995(Manthey et al , 1997. In addition, phytotoxicity of herbicides applied in four drops was similar for all MVO concentrations despite increased droplet spread with increased MVO concentrations.…”
Section: Resultsmentioning
confidence: 70%
“…Phytotoxicity has been related to surfactant structure (ionic surfactants being more phytotoxic) and EO content (low EOs being more phytotoxic than higher EOs). Certain oils and emulsifier combinations have also been shown to be particularly harmful at times ( Falk et al ., 1994 ; Gaskin, 1995; Manthey et al ., 1997 ).…”
Section: Formulation Characteristics and Effectsmentioning
confidence: 99%